Respuestas
Respuesta dada por:
4
4x-3y=6......................1
3x+2y=13...................2
de 1 despejamos y
3y=4x-6
y=4/3x-6/3.................y=4/3x-2.............3
sustituímos 3 en 2
3x + 2(4/3x-2)=13
3x + 8/3x -4 =13
MCM=3
9x +8x-12 =39
17x=51...........x=3..........
y=(4/3*3)-2........y=2
3x+2y=13...................2
de 1 despejamos y
3y=4x-6
y=4/3x-6/3.................y=4/3x-2.............3
sustituímos 3 en 2
3x + 2(4/3x-2)=13
3x + 8/3x -4 =13
MCM=3
9x +8x-12 =39
17x=51...........x=3..........
y=(4/3*3)-2........y=2
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años